Enhancing Environmental Stewardship in Life Sciences ‎Education: Integrating Project-Based Learning and ‎Nanotechnology Perspectives - Miroshnichenko, Valentyna; Adamchuk , Yuliya; Dziuba , Petro; Bilorus , Andrii; Filippov , Maksym; Demskyi, Valentyn (International Journal of Basic and Applied Sciences, 2025)
Addressing escalating global environmental challenges necessitates professionals equipped with both specialized knowledge and a strong ‎sense of environmental responsibility. This study investigates an innovative educational approach integrating Project-Based Learning (PBL) ‎with perspectives on nanotechnology applications to cultivate environmental culture among learners pursuing professional qualifications ‎potentially related to life and environmental sciences. PBL engages students in authentic problem-solving related to environmental issues, ‎fostering critical thinking and collaborative skills essential for life science careers. Introducing nanotechnology concepts provides insights ‎into cutting-edge solutions for environmental remediation, monitoring, and resource efficiency (e.g., water purification, sustainable ‎agriculture). We implemented an educational intervention involving learners (n=112 in experimental group, n=115 in control) and assessed ‎changes in their environmental culture using predefined criteria (motivational-value, informational-cognitive, resultative-pragmatist). Pre- ‎and post-intervention assessments revealed statistically significant improvements in all criteria for the experimental group exposed to the ‎integrated PBL-nanotechnology approach compared to the control group. The findings suggest that combining active learning methodologies ‎like PBL with forward-looking technological perspectives like nanotechnology can effectively enhance learners’ environmental awareness, ‎understanding of sustainability principles, and preparedness to act as environmentally conscious professionals within life science and related ‎fields. This approach holds promise for developing future leaders capable of contributing to sustainable development goals‎.